Pnictogen Semimetal (Sb, Bi)-Based Nanomaterials for Cancer Imaging and Therapy: A Materials Perspective - Yu, Xujiang; Liu, Xinyi; Yang, Kai; Chen, Xiaoyuan; Li, Wanwan (ACS nano, 2021)
Innovative multifunctional nanomaterials have attracted tremendous interest in current research by facilitating simultaneous cancer imaging and therapy. Among them, antimony (Sb)- and bismuth (Bi)-based nanoparticles are important species with multifunction to boost cancer theranostic efficacy. Despite the rapid development, the extensive previous work treated Sb- and Bi-based nanoparticles as mutually independent species, and therefore a thorough understanding of their relationship in cancer theranostics was lacking. We propose here that the identical chemical nature of Sb and Bi, being semimetals, provides their derived nanoparticles with inherent multifunction for near-infrared laser-driven and/or X-ray-based cancer imaging and therapy as well as some other imparted functions. An overview of recent progress on Sb- and Bi-based nanoparticles for cancer theranostics is provided to highlight the relationship between chemical nature and multifunction. The understanding of Sb- and Bi-based nanoparticles in this way might shed light on the further design of smart multifunctional nanoparticles for cancer theranostics.